QUALITY EVALUATION ON POST-HARVEST CORN COMMODITIES PHYSICALLY, CHEMICALLY AND BIOLOGICALLY PRODUCED BY FARMERS IN GROBOGAN DISTRICT - Nur Muttaqien Zuhri (Agros Journal of Agriculture Science, 2022)
Handling post-harvest corn yield is the determinant of the quality of raw materials in feed manufacturing. The high quality standard of the acceptance of raw materials in the livestock industry makes it difficult for post-harvest corn yield produced by farmers to compete. The objective of this research is to evaluate the quality of corn yield physically, chemically and biologically by comparing the quality of post-harvest corn yield produced by farmers in Grobogan District with the corn yield of feed industry. Physical testing (broken seed and foreign material) was carried out using human senses, chemical testing (moisture content, protein, fiber, ash) was carried out using NIR Foss System and biological testing (aflatoxin) was carried out using TLC method. The data analysis was performed using Independent Sampel T-Test. The research findings showed that there were differences (P < 0.05) to the average quality of broken seed, foreign material, moisture content, fiber, ash and aflatoxy between the farmers and livestock industry. Meanwhile, there was no significant difference (P > 0.05) to the average value of quality of protein and fat content between the farmers and livestock industry. Post-harvest corn yield produced by farmers has not met the standard of the acceptance of raw materials in livestock industry. It is also necessary to improve the modern technology, facility and farmer assistance in handling post-harvest activities of the corn yield.